Endurance of methanogenic archaea in anaerobic bioreactors treating oleate-based wastewater - Salvador, A. F. (2013)
Methanogenic archaea are reported as very sensitive to lipids and long chain fatty acids (LCFA). Therefore, in conventional anaerobic processes, methane recovery during LCFA-rich wastewater treatment is usually low. By applying a start-up strategy, based on a sequence of step feeding and reaction cycles, an oleate-rich wastewater was efficiently treated at an organic loading rate of 21 kg COD m(-3) day(-1) (50 % as oleate), showing a methane recovery of 72 %. In the present work, the archaeal community developed in that reactor is investigated using a 16S rRNA gene approach. This is the first time that methanogens present in a bioreactor converting efficiently high loads of LCFA to methane are monitored. Denaturing gradient gel electrophoresis profiling showed that major changes on the archaeal community took place during the bioreactor start-up, where phases of continuous feeding were alternated with batch phases. After the start-up, a stable archaeal community (similarity higher than 84 %) was observed and maintained throughout the continuous operation. This community exhibited high LCFA tolerance and high acetoclastic and hydrogenotrophic activity. Cloning and sequencing results showed that Methanobacterium- and Methanosaeta-like microorganisms prevailed in the system and were able to tolerate and endure during prolonged exposure to high LCFA loads, despite the previously reported LCFA sensitivity of methanogens.